Marked Epitope- and Allele-Specific Differences in Rates of Mutation in Human Immunodeficiency Type 1 (HIV-1) Gag, Pol, and Nef Cytotoxic T-Lymphocyte Epitopes in Acute/Early HIV-1 Infection - Brumme, Zabrina L.; Brumme, Chanson J.; Carlson, Jonathan M.; Streeck, Hendrik; John, Mina; Eichbaum, Quentin; Block, Brian L.; Baker, Brett; Kadie, Carl; Markowitz, Martin; Jessen, Heiko; Kelleher, Anthony D.; et al. (Journal of Virology, 2008)
During acute human immunodeficiency virus type 1 (HIV-1) infection, early host cellular immune responses drive viral evolution. The rates and extent of these mutations, however, remain incompletely characterized. In a cohort of 98 individuals newly infected with HIV-1 subtype B, we longitudinally characterized the rates and extent of HLA-mediated escape and reversion in Gag, Pol, and Nef using a rational definition of HLA-attributable mutation based on the analysis of a large independent subtype B data set. We demonstrate rapid and dramatic HIV evolution in response to immune pressures that in general reflect established cytotoxic T-lymphocyte (CTL) response hierarchies in early infection. On a population level, HLA-driven evolution was observed in [ ]80% of published CTL epitopes. Five of the 10 most rapidly evolving epitopes were restricted by protective HLA alleles (HLA-B*13/B*51/B*57/B*5801; P=0.01), supporting the importance of a strong early CTL response in HIV control. Consistent with known fitness costs of escape, B*57-associated mutations in Gag were among the most rapidly reverting positions upon transmission to non-B*57-expressing individuals, whereas many other HLA-associated polymorphisms displayed slow or negligible reversion. Overall, an estimated minimum of 30% of observed substitutions in Gag/Pol and 60% in Nef were attributable to HLA-associated escape and reversion events. Results underscore the dominant role of immune pressures in driving early within-host HIV evolution. Dramatic differences in escape and reversion rates across codons, genes, and HLA restrictions are observed, highlighting the complexity of viral adaptation to the host immune response.